Administration of Hookworm Excretory/Secretory Proteins Improves Glucose Tolerance in a Mouse Model of Type 2 Diabetes - Zainab Khudhair; Rafid Alhallaf; Ramon M. Eichenberger; Matt Field; Lutz Krause; Javier Sotillo; Alex Loukas (Biomolecules, 2022)
Diabetes is recognised as the world’s fastest growing chronic condition globally. Helminth infections have been shown to be associated with a lower prevalence of type 2 diabetes (T2D), in part due to their ability to induce a type 2 immune response. Therefore, to understand the molecular mechanisms that underlie the development of T2D-induced insulin resistance, we treated mice fed on normal or diabetes-promoting diets with excretory/secretory products (ES) from the gastrointestinal helminth Nippostrongylus brasiliensis. We demonstrated that treatment with crude ES products from adult worms (AES) or infective third-stage larvae (L3ES) from N. brasiliensis improved glucose tolerance and attenuated body weight gain in mice fed on a high glycaemic index diet. N. brasiliensis ES administration to mice was associated with a type 2 immune response measured by increased eosinophils and IL-5 in peripheral tissues but not IL-4, and with a decrease in the level of IL-6 in adipose tissue and corresponding increase in IL-6 levels in the liver. Moreover, treatment with AES or L3ES was associated with significant changes in the community composition of the gut microbiota at the phylum and order levels. These data highlight a role for N. brasiliensis ES in modulating the immune response associated with T2D, and suggest that N. brasiliensis ES contain molecules with therapeutic potential for treating metabolic syndrome and T2D.